(untitled) (Experimental biology, 2022)
This article presents a histological study of the gills, liver of carp and zander living in Lake Balkhash. On the basis of the revealed extensive morphological changes of a destructive nature in the gills and liver of carp and zander, it was concluded that this reservoir was polluted with toxicants. The article presents the morphological and functional characteristics and general assessment of the influence of environmental factors on the cyto- and histostructure of the gills and liver of carp and zander. Differences were revealed at the comparative histological level of the morphostructure of the gills and liver of these fish. In the fish liver, there is a swelling of blood vessels, rupture of the walls of blood vessels. Some veins were deformed. Dystrophic changes are observed in vacuoles. There was an excess of blood in the vessels, blood stagnation. Parenchymal cells are moderately swollen. The number of Kupffer cells increased. On many optically empty "vacuoles" in the form of bubbles with dense boundaries, edematous degeneration (vacuolar dystrophy) is observed. The hepatic rays were located radially. The intercellular space was filled with lymphocytes and macrophages. This indicates a decrease in the transport of the liver from the lymph. Microcirculation in the canal is disturbed. Blood stagnation was observed in the central arteries; optically empty vacules were susceptible to hydropic degeneration. In the studied individuals of carp and zander, the gills, represented by the branchial lobes and branchial lobes extending from them, had the following morphological structure. In the studied zander individuals, morphological changes of a destructive nature in the gills were noted. They were expressed in a change in the shape of the lamellae, extensive necrosis of the secondary branchial epithelium, destruction of the vascular layer of the lamellae with the formation of hemorrhages and hemorrhages.